2011
DOI: 10.1016/j.schres.2011.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and outcome of auditory hallucinations in adolescence: A longitudinal general population study of 1800 individuals

Abstract: Although hallucinations in adolescents are a common and mainly transitory phenomenon, the persistence rate over time is far from negligible, and associated with clinical deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 36 publications
8
68
0
3
Order By: Relevance
“…This compares to a median prevalence of 5% reported by van Os and colleagues in a meta analysis of mainly adult studies of psychotic symptoms, which supports the idea that psychotic symptoms are more prevalent in childhood compared to adulthood. This is also in line with longitudinal research, which has shown a decline in the incidence of psychotic symptoms in young people followed over time (Bartels-Velthuis et al, 2011, De Loore et al, 2011, Dominguez et al, 2011, Mackie et al, 2011.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This compares to a median prevalence of 5% reported by van Os and colleagues in a meta analysis of mainly adult studies of psychotic symptoms, which supports the idea that psychotic symptoms are more prevalent in childhood compared to adulthood. This is also in line with longitudinal research, which has shown a decline in the incidence of psychotic symptoms in young people followed over time (Bartels-Velthuis et al, 2011, De Loore et al, 2011, Dominguez et al, 2011, Mackie et al, 2011.…”
Section: Discussionsupporting
confidence: 89%
“…A total of 19 studies met criteria for inclusion -5 interview studies (Horwood et al, 2008, Kelleher et al, 2008, Kelleher et al, In Press, Polanczyk et al, 2010, Poulton et al, 2000 and 14 self report questionnaire studies (Barragan et al, 2011, De Loore et al, 2011, Dhossche et al, 2002, Kelleher et al, In Press, Kinoshita et al, 2011, Lataster et al, 2006, Scott et al, 2009a, Scott et al, 2009b, Wigman et al, 2011, Yoshizumi et al, 2004, Yung et al, 2009) (see Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…At follow-up, on average two years later, the PLE prevalence was 30% and within the prevalence range (15-38%) reported by several large urban adolescent cohort samples using self-report questionnaires De Loore et al, 2011;Dominguez et al, 2011;Kelleher et al, 2011). Only 39% of children who originally reported PLEs continued to do so two years later.…”
Section: Prevalence Of Plessupporting
confidence: 60%
“…Longitudinal studies following adolescents into adulthood distinguish short-lived or transitory PLEs that may be relatively benign from persistent PLEs that impose a greater likelihood of concurrent, and later, psychiatric morbidity and social impairment (Cougnard et al, 2007;Woods et al, 2009;Dominguez et al, 2011). Recent longitudinal work employing adolescent samples indicates that persistent PLE trajectories, compared with non-persistent trajectories, are associated with the highest levels of internalising psychopathology (i.e., symptoms of anxiety, depression, or social withdrawal) at follow-up (Mackie et al, 2010;De Loore et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation